Striving for excellence in experiential education. Issue 3 (17th April 2020) - Boyce, Eric G.; Harris, Christy S.; Bingham, Angela L.; Chan, Emily; Chapman, Scott A.; Chilbert, Maya R.; Dy‐Boarman, Eliza; Haines, Stuart T.; Heavner, Mojdeh S.; Marcus, Kristine B.; Smith, Susan E.; Strnad, Kyle; et al.
Abstract: High‐quality experiential education builds on didactic education to enable graduates to meet the full spectrum of entry‐level pharmacy‐related roles and responsibilities, including lifelong learning and professional development. The 2019 Educational Affairs Committee A, an ACCP standing committee, was charged to review and update the 2008 ACCP white paper and position statement on quality experiential education. The main objective of this white paper is to provide colleges and schools of pharmacy (C/SOPs) and affiliated partners in experiential education with practices expected to assist in achieving excellence in experiential education and fulfilling the goal of developing fully competent practice‐ and team‐ready pharmacy graduates.